Development of Pyroshock Simulator for Shock Propagation Test. (13th September 2018) - Lee, So-Jeong; Hwang, Dae-Hyun; Han, Jae-Hung
Abstract : Satellites are subjected to pyrotechnic shocks caused by actuating the pyrotechnic separation devices during various missions such as separation from the launch vehicle and deployment of the solar panel. Pyroshock rarely damages structural members, but it may cause damage to mounted electronic equipment, which can lead to mission failures. In order to protect electronic equipment from pyroshock, shock propagation characteristics need to be identified. This paper proposes a compact pyroshock simulator that can be used to identify the pyroshock propagation characteristics at various locations of a structure. A small resonant fixture and high air pressure are used to make the simulator compact in size. A diaphragm breech design is also introduced to achieve high-bursting pressure and increase the repeatability of the simulator. The developed simulator can produce the pyroshock environment with repeatability in the shock propagation path, and also the pyroshock environment can be changed by using different resonant fixtures. The developed simulator can be used for the experimental characterization of the pyroshock propagation over various structures.